Prognostic significance of troponin increment after percutaneous coronary intervention: A retrospective study - Li, Ya; Li, Duanbin; Zhao, Liding; Xu, Tian; Lv, Qingbo; He, Jialin; Wang, Yao; Zhang, Wenbin (Frontiers in Cardiovascular Medicine, 2022)
Objective: The prognostic significance of troponin elevation following percutaneous coronary intervention (PCI) remains debated. This study aimed to evaluate the association between different thresholds of post-PCI cardiac troponin I (cTnI) and mortality. Methods: From January 2012 to July 2017, 5,218 consecutive patients undergoing elective PCI with pre-PCI cTnI <99th percentile the upper reference limit (URL) were included. Levels of cTnI were measured before PCI, and every 8 hours for 24 hours after procedural. The outcomes were 3-year cardiac mortality. Results: Patients had a mean age of 66.2 years, 27.6% were female, 67.0% had hypertension, and 26.2% had diabetes mellitus. During the three years of follow-up, cardiac death occurred in 0.86%, 1.46%, 1.69%, 2.26% and 2.86% of patients with cTnI <1, ≥1 to <5, ≥5 to <35, ≥35 to <70, and ≥70 times URL. Cardiac mortality rate moderately increased with higher peak cTnI values, but the Kaplan-Meier curve demonstrated no significant association between any elevation of cTnI and either cardiac or non-cardiac mortality. Isolated cTnI elevation ≥5×URL, ≥35×URL, and ≥70×URL occurred in 70 (1.4%), 197 (3.9%), and 1379 (26.4%) patients, respectively. In multivariate Cox regression analysis and Fine-Gray model, none of the above cTnI thresholds was significantly associated with an increased risk of cardiac death. Conclusions: In patients undergoing elective PCI, post-PCI cTnI elevation is not independently associated with cardiac mortality.